Qualitative Review on the Negative Effects of Facebook Towards Mental Health - Yap, Yuan Teng; Soon, Eu Hui; Tan, Foong Ping; Yuan, Xiaodong (INTI International University, 2024)
This study investigates the negative impacts of Facebook use on mental health, with a focus on its implications for achieving Sustainable Development Goal 3 (SDG 3): ensuring good health and well-being for all. As a dominant force in social media, Facebook has profoundly influenced societal behaviors and individual lifestyles since its inception. However, its pervasive use has been linked to mental health outcomes, including increased anxiety, depression, and feelings of social isolation. Through an exploration of behavioral patterns and psychological responses associated with excessive Facebook use, this study aims to uncover the subtle yet significant ways in which the platform may undermine mental well-being. The findings are expected to offer actionable insights into how prolonged social media engagement contributes to deteriorating mental health, particularly among vulnerable populations. Additionally, this study examines how demographic factors, such as age, mediating the relationship between Facebook use and mental health, highlighting disparities that challenge the universality of SDG 3. By raising awareness of the potential mental health risks posed by social media, this research underscores the urgency of fostering digital literacy and promoting healthier online habits as part of a broader effort to achieve mental well-being globally. Ultimately, the study advocates for a more balanced integration of social media into daily life to support the overarching goals of SDG 3.